Interaction of S-layer proteins of Lactobacillus kefir with model membranes and cells - Hollmann, Axel (2017)
In previous works, it was shown that S-layer proteins from Lactobacillus kefir were able to recrystallize and stabilize liposomes, this feature reveling a great potential for developing liposomal-based carriers. Despite previous studies on this subject are important milestones, a number of questions remain unanswered; In this context, the feasibility of S-layer proteins as a biomaterial for drug delivery was evaluated in this work. First, S-layer proteins were fully characterized by Electron microscopy, 2D-electrophoresis, and HPAEC-PAD. Afterward, interactions of S-layer proteins with model lipid membranes were evaluated, showing that proteins adsorb to the lipid surface following a non-fickean or anomalous diffusion, when positively charged lipid were employed, suggesting that electrostatic interaction is a key factor in the recrystallization process on these proteins. Finally, the interaction of S-layer coated liposomes with CACO-2 cell line was assessed, First cytotoxicity of formulations was tested showing noncytotoxic effects in S-layer coated vesicles. Second, by flow cytometry, it was observed an increased ability to transfer cargo molecules into CACO-2 cells from S-layer coated liposomes in comparison to control ones. All data put together, supporting the idea that a combination of adhesive properties of S-layer proteins concomitant with higher stability of S-layer coated liposomes represents an exciting starting point in the development of new drug carriers.